Negative electrode material, preparation method thereof and secondary battery
By creating porous graphite through high-temperature water vapor etching, the method addresses the low-temperature performance issue in lithium-ion batteries by enhancing lithium ion diffusion and reducing impedance, thus improving battery performance in cold conditions.
Patent Information
- Application Number
- CN202310722091.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
AI Technical Summary
Lithium-ion batteries exhibit reduced charging and discharging performance in low-temperature environments, primarily due to the inability to improve the diffusion of lithium ions within graphite particles, which affects their normal use in severe cold areas and harsh natural conditions.
A method involving material mixing and water vapor etching is employed to create porous graphite by dispersing graphite and transition metal salts in a solvent, followed by drying and high-temperature water vapor etching to form channels within the graphite particles, reducing lithium ion diffusion distance and impedance.
The method enhances lithium ion diffusion and reduces impedance, thereby improving the low-temperature performance of lithium-ion batteries without compromising the material's gram capacity.
Smart Images

Figure CN119153692A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a negative electrode material and a preparation method thereof, and a secondary battery. Background Art
[0002] At present, energy and environmental problems are becoming increasingly serious. The shortage of oil resources and the air pollution caused by automobile combustion have become a major problem in today's society. Studies have shown that the energy utilization efficiency of crude oil-powered cars is higher than that of gasoline-powered cars after crude oil refinement. Therefore, electric vehicles are conducive to saving energy and reducing carbon dioxide emissions. At the same time, electric vehicles use electricity as a driving force. In addition to the original power generation of crude oil, there are many new energy power generation methods such as geothermal, wind, tidal, solar energy, etc. This has proposed effective solutions to the energy crisis we are currently facing.
[0003] At present, the energy storage batteries of new energy electric vehicles are mainly lithium batteries. The batteries of the current mainstream technology route are lithium-ion batteries assembled from ternary materials or lithium iron phosphate and graphite negative electrodes. Lithium-ion batteries have advantages such as good high-temperature performance, high safety, long cycle life, good safety performance, low self-discharge rate, and no memory effect. However, in low-temperature environments, their charging and discharging performance is greatly reduced, which seriously affects their normal use in severe cold areas and harsh natural environments. Therefore, the low-temperature charging and discharging performance of lithium-ion batteries needs to be improved urgently.
[0004] At present, the methods to improve the low-temperature performance of lithium-ion batteries mainly include: improving the electrolyte composition to increase the low-temperature conductivity of the electrolyte, coating the negative electrode with carbon graphite to improve the negative electrode kinetics, using high-kinetic negative electrode auxiliary materials to improve the negative electrode kinetics, etc. Although these approaches can improve the negative electrode kinetics to a certain extent, they can only improve the transmission of lithium ions in the electrolyte, the negative electrode sheet and the surface of the graphite particles, but cannot improve the diffusion of lithium ions inside the graphite particles. Summary of the invention
[0005] In view of the above shortcomings of the prior art, the present invention provides a negative electrode material and a preparation method thereof and a secondary battery to improve the transmission of lithium ions inside graphite particles and reduce the diffusion distance of lithium ions in graphite particles.
[0006] To achieve the above-mentioned purpose and other related purposes, the present invention provides a method for preparing a negative electrode material, which includes material mixing and water vapor etching steps. The material mixing includes: dispersing graphite and transition metal salt in a dispersant, stirring and compounding, and then drying to obtain a precursor; the water vapor etching includes: placing the precursor in a furnace, and passing water vapor into the furnace for etching reaction to obtain porous graphite.
[0007] In one example of the present invention, the transition metal salt includes one or more of transition metal nitrates, transition metal carbonates, transition metal acetates, nickel acetylacetonate, and cobalt acetylacetonate.
[0008] In one example of the present invention, the general formula of the transition metal nitrate is M(NO3): x1 The general formula of the transition metal carbonate is M(CO3) x2 The general formula of the transition metal acetate is M(CH3COO) x3 , wherein M represents a transition metal, and the M is selected from any one of Co, Ni, Mn, and Cr, and x1≥2, x2≥1, and x3≥2.
[0009] In an example of the present invention, the molar ratio of the transition metal salt to the graphite is 0.02% to 0.03%.
[0010] In an example of the present invention, the dispersant includes one or more of water, ethanol and N,N-dimethylformamide.
[0011] In an example of the present invention, the water vapor etching step specifically includes:
[0012] Heating stage: placing the precursor in a tube furnace, and introducing an inert gas into the tube furnace, so that the tube furnace is heated to a target temperature in an inert atmosphere;
[0013] Reaction stage: after the tube furnace is heated to the target temperature, water vapor is introduced into the tube furnace, and an etching reaction is performed at the target temperature;
[0014] Cooling stage: After the etching reaction is completed, the introduction of water vapor is suspended to allow the temperature of the tubular furnace to drop to room temperature in an inert atmosphere.
[0015] In an example of the present invention, in the heating stage, the heating rate of the tube furnace is 5 to 10°C / min, and the target temperature of the tube furnace is 800 to 900°C.
[0016] In an example of the present invention, in the reaction stage, the volume ratio of the water vapor to the inert gas is 1:9, and the reaction time of the etching reaction is 6 to 8 hours.
[0017] In one example of the present invention, the drying temperature in the material mixing step is lower than 60°C.
[0018] Another aspect of the present invention further provides a negative electrode material, which is prepared by the above-mentioned preparation method.
[0019] In an example of the present invention, the negative electrode material includes porous graphite, and the pores in the porous graphite extend from the surface of the graphite particles to the interior of the graphite particles.
[0020] The present invention also provides a secondary battery, which comprises a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the negative electrode plate comprises the negative electrode material prepared by the above preparation method.
[0021] The present invention utilizes high-temperature water vapor etching technology to etch graphite to create channels inside the graphite particles. Lithium ions can quickly diffuse into the graphite particles through the channels, reducing the transmission distance and transmission impedance of lithium ions in the graphite particles and improving the kinetic performance, thereby greatly improving the low-temperature performance of the graphite material without reducing the gram capacity of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 is a flow chart of the preparation method of the negative electrode material of the present invention;
[0024] Figure 2 The figure is a flow chart of the water vapor etching step in one embodiment of the method for preparing the negative electrode material of the present invention. DETAILED DESCRIPTION
[0025] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0026] For simplicity, only some numerical ranges are explicitly disclosed herein, and each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unspecified range.
[0027] See also Figure 1 and Figure 2 The present invention provides a negative electrode material, a preparation method thereof and a secondary battery, which utilizes high-temperature water vapor etching technology to etch channels inside graphite particles to reduce the transmission distance and transmission impedance of lithium ions inside the graphite particles and improve the low-temperature performance of the graphite material.
[0028] See also Figure 1 The method for preparing the negative electrode material of the present invention comprises at least the following steps:
[0029] S1. Material mixing: dispersing graphite and transition metal salt in a solvent, stirring and compounding, and then drying to obtain a precursor;
[0030] S2. Water vapor etching: placing the precursor in a furnace, and introducing water vapor into the furnace to perform an etching reaction to obtain porous graphite.
[0031] Specifically, the graphite in step S1 is selected from graphite negative electrode materials commonly used in the art, which can be purchased through general commercial channels or prepared according to conventional preparation methods, and is not limited here.
[0032] The transition metal salt is selected from salts that are easily decomposed into transition metal oxides. Since the transition metal salt can be decomposed into transition metal oxides at high temperatures, the transition metal oxides can act as catalysts to promote the etching reaction between carbon and water vapor in the graphite to form pores inside the graphite particles.
[0033] In some embodiments, the transition metal salt is selected from transition metal nitrates, transition metal carbonates, transition metal acetates and other easily decomposable salts, wherein the general formula of the transition metal nitrate is M(NO3): x1 , the general formula of transition metal carbonate is M(CO3) x2 , the general formula of transition metal acetate is M(CH3COO) x3 In the above structural formula, M represents a transition metal, and M is selected from any one of Co, Ni, Mn, and Cr, and x1≥2, x2≥1, and x3≥2; other easily decomposed salts include nickel acetylacetonate, cobalt acetylacetonate, and the like. In other words, transition metal salts include M(NO3) x1 (M=Co, Ni, Mn, Cr, x1≥2), M(CO3) x2 (M=Co, Ni, Mn, Cr, x2≥1), M(CH3COO)x3 (M=Co, Ni, Mn, Cr, x≥2), one or more of nickel acetylacetonate, cobalt acetylacetonate, that is, the transition metal salt can be selected from any one of the above salts, such as Co(NO3)2, or Co(CH3COOH)2, or Ni(NO3)2, etc.; the transition metal salt can also be selected from any two or more combinations of the above salts, such as a combination of nickel acetylacetonate and cobalt acetylacetonate, or a combination of Co(NO3)2 and Ni(NO3)2, or a combination of MnCO3, Ni(NO3)2 and Cr(CH3COO)3, or a combination of Ni(NO3)2 and Ni(CH3COO)2, etc. It should be noted that when the transition metal salt is a composition, there is no restriction on the ratio between the components in the composition, and they can be mixed in any ratio. Of course, the transition metal salt can also be selected from the easily decomposable salts not listed above.
[0034] The dispersant in step S1 mainly serves to accommodate graphite and transition metal salts, can evenly disperse graphite and transition metal salts, and prevent particle sedimentation and agglomeration. The type of dispersant is not limited here. As an example, the dispersant can be selected from one or more of water, ethanol and N,N-dimethylformamide, that is, the dispersant can be a single reagent, such as water, or ethanol, or N,N-dimethylformamide, etc.; the dispersant can also be a combination of two or more reagents mixed in any proportion, such as a combination of water and ethanol, or a combination of water and N,N-dimethylformamide, or a combination of water, ethanol and N,N-dimethylformamide, etc. Of course, the dispersant can also be selected from other unlisted reagents, and any reagent that can evenly disperse graphite and transition metal salts belongs to the protection scope of this application.
[0035] The graphite and transition metal salt can be dispersed in the dispersant by a conventional dispersion method in the art, for example, adding the graphite and transition metal salt into a container containing the dispersant, stirring and dispersing for 2 hours to form a stable dispersion system. The amount of the dispersant added is not limited, as long as the graphite and transition metal salt can be fully dispersed. The molar ratio of the transition metal salt to the graphite is 0.02% to 0.03%, for example, the molar ratio of the transition metal salt to the graphite can be 0.02%, 0.025% or 0.03%, etc.
[0036] After the graphite and the transition metal salt are uniformly dispersed in the dispersant, they are dried to obtain a mixture of graphite and the transition metal salt. It should be noted that the drying temperature here shall not exceed 60°C, and it can be 60°C, 50°C, 30°C, etc. Considering the drying time, the drying temperature is preferably 60°C. The drying method can be a vacuum drying oven or other drying equipment commonly used in the art.
[0037] See also Figure 1 and Figure 2 Step S2, the water vapor etching step specifically includes:
[0038] S21, heating stage: placing the precursor in a tube furnace, and introducing an inert gas into the tube furnace, so that the tube furnace is heated to a target temperature in an inert atmosphere;
[0039] S22, reaction stage: after the tube furnace is heated to the target temperature, water vapor is introduced into the tube furnace, and an etching reaction is performed at the target temperature;
[0040] S23, cooling stage: after the etching reaction is completed, the introduction of water vapor is suspended to allow the temperature of the tubular furnace to drop to room temperature in an inert atmosphere.
[0041] Step S21 is to put the mixture of graphite and transition metal salt prepared in step S1 into a tube furnace, and introduce an inert gas, such as nitrogen, helium or argon, into the tube furnace to heat the tube furnace to a target reaction temperature of 800 to 900°C, such as 850°C, in an inert atmosphere; wherein the heating rate of the tube furnace is 5 to 10°C / min, for example, the heating rate can be selected as 5°C / min, 8°C / min or 10°C / min, etc. It should be noted that since the transition metal salt is an easily decomposable salt, it is easy to decompose into transition metal oxides at high temperatures. Depending on the type of salt, it begins to decompose at more than 300°C. The decomposed transition metal oxide can act as a catalyst to promote the etching reaction of carbon and water vapor in graphite.
[0042] Step S22, when the temperature in the tube furnace reaches the target reaction temperature, water vapor is introduced while the inert gas is kept introduced, so that the water vapor etches the graphite at high temperature (C+H2O=CO+H2), so as to etch a channel extending from the surface to the inside of the graphite particles. At this stage, the volume ratio of the introduced water vapor to the volume of the inert gas is 1:9, and the etching reaction time is 6 to 8 hours, for example, 6 hours, 7 hours or 8 hours, etc. The specific reaction time can be selected according to actual needs.
[0043] Step S23, after the etching reaction is completed, the introduction of water vapor is stopped, the inert gas is kept unchanged, and the tubular furnace is allowed to reach room temperature in the inert atmosphere to obtain the final product, porous graphite.
[0044] Since a small amount of transition metal salt is added in step S1, when the temperature of the tube furnace rises to above 300°C, the transition metal salt begins to decompose to produce transition metal oxides, which can act as catalysts to promote the etching reaction between water vapor and graphite. Therefore, a small amount of transition metal oxides (less than 0.01%) may exist in the final product of the etching reaction and adhere to the graphite surface, which will not affect the pores inside the graphite.
[0045] The negative electrode material provided by the present invention is prepared by the above-mentioned preparation method.
[0046] The above-mentioned negative electrode material includes porous graphite, and the pores in the porous graphite extend from the surface of the graphite particles to the inside of the graphite particles. When it is used as a negative electrode material in a lithium-ion secondary battery, lithium ions can quickly diffuse into the inside of the graphite particles through the pores, reducing the diffusion distance of lithium ions in the graphite particles, thereby reducing the negative electrode impedance and improving the kinetic performance.
[0047] The secondary battery provided by the present invention comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode material prepared by the above-mentioned preparation method. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet; the separator separates the positive electrode sheet and the negative electrode sheet, and the electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0048] Specifically, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode current collector has a material with good conductivity and mechanical strength, and plays the role of conducting and collecting current. The negative electrode current collector can adopt the conventional current collector type of the present invention, such as copper foil. The negative electrode active material layer includes the negative electrode material, negative electrode conductive agent, negative electrode binder and thickener of the present invention, wherein the negative electrode conductive agent, negative electrode binder and thickener can all be selected from conventional material types in the art. As an example, the negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more mixed in any proportion. The negative electrode binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR) or several combinations mixed in any proportion; the thickener is selected from carboxymethyl cellulose (CMC), which can be sodium carboxymethyl cellulose (CMC-Na) or lithium carboxymethyl cellulose (CMC-Li).
[0049] The negative electrode sheet can be prepared according to methods known in the art. For example, the negative electrode material, negative electrode binder, thickener and negative electrode conductive agent are dispersed in deionized water to form a uniform negative electrode slurry: the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet is obtained. Among them, the ratio between the components in the negative electrode slurry can be set according to the conventional ratio, and is not limited here.
[0050] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode current collector can be made of a material with good conductivity and mechanical strength, such as aluminum foil. The positive electrode active material layer includes a positive electrode material, a positive electrode conductive agent and a positive electrode binder. The specific type of the positive electrode material is not specifically limited here. The materials known in the art that can be used for the positive electrode of a secondary battery can be used. Those skilled in the art can choose according to actual needs. For example, if the secondary battery is a lithium-ion secondary battery, the positive electrode material may include a lithium transition metal oxide or a lithium-containing phosphate. Specifically, the lithium transition metal oxide includes but is not limited to lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel oxide, lithium cobalt oxide, lithium nickel cobalt oxide, etc.; lithium-containing phosphates include but are not limited to lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, etc. The positive electrode binder can be selected from conventional binder types in the art, such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), etc. The positive electrode conductive agent can be selected from conventional conductive agents in the art, such as one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more of them mixed in any proportion.
[0051] The positive electrode sheet can be prepared according to methods known in the art. As an example, the positive electrode material, the positive electrode conductive agent and the positive electrode binder are dispersed in a solvent (such as N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry: the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet is obtained. The ratio between the components in the positive electrode slurry can be set with reference to the conventional ratio, and is not limited here.
[0052] The diaphragm is selected from conventional types in the art, for example, a PE porous membrane is selected as the diaphragm, the thickness of the diaphragm is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.
[0053] The electrolyte is selected from a conventional combination type in the art, which includes an organic solvent, an electrolyte salt (selected according to the type of battery, for example, a lithium salt is selected for a lithium battery) and an additive, wherein the solvent can be selected from one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), etc., or a mixture of several of them in any proportion. The lithium salt is selected from one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalate borate), LiBOB (lithium dioxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalate phosphate), LiTFOP (lithium tetrafluorooxalate phosphate) or a combination thereof in any proportion. The additive may include a film-forming additive and a functional additive that can improve battery performance. The specific types of additives are not described one by one here, and those skilled in the art may select according to actual needs.
[0054] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0055] Example 1
[0056] Cobalt acetate and graphite are dispersed in water at a molar ratio of 0.025%, stirred at high speed for uniform dispersion, and then dried to obtain a precursor of graphite and cobalt acetate composite; the precursor is placed in a tubular furnace, and inert gas nitrogen is introduced into the furnace, and the temperature is increased to 850°C at a heating rate of 10°C / min under a nitrogen atmosphere; then water vapor is introduced (the volume ratio of water vapor to nitrogen at this stage is 1:9), and the reaction is carried out at this temperature for 6 hours; after the reaction is completed, the introduction of water vapor is stopped, and the temperature is lowered to room temperature under a nitrogen atmosphere to obtain porous graphite.
[0057] Example 2
[0058] The difference between this embodiment and embodiment 1 is that cobalt acetate is replaced by cobalt acetylacetonate.
[0059] Example 3
[0060] The difference between this embodiment and embodiment 1 is that the etching reaction time is 8 hours.
[0061] Example 4
[0062] The difference between this embodiment and embodiment 1 is that the molar ratio of cobalt acetate to graphite is 0.02%.
[0063] Example 5
[0064] The difference between this embodiment and embodiment 1 is that the molar ratio of cobalt acetate to graphite is 0.03%.
[0065] Example 6
[0066] The difference between this embodiment and embodiment 1 is that cobalt acetate is replaced by nickel nitrate, and the etching reaction time is 7 hours.
[0067] Comparative Example 1
[0068] Graphite was dispersed in water, stirred at high speed until evenly dispersed and then dried; then it was placed in a tubular furnace, and inert gas nitrogen was introduced into the furnace, and the temperature was raised to 850°C at a heating rate of 10°C / min in a nitrogen atmosphere; then water vapor was introduced (the volume ratio of water vapor to nitrogen at this stage was 1:9), and the reaction was carried out at this temperature for 6 hours; after the reaction was completed, the introduction of water vapor was stopped, and the temperature was lowered to room temperature in a nitrogen atmosphere.
[0069] Comparative Example 2
[0070] Cobalt acetate and graphite are dispersed in water at a molar ratio of 0.025%, and the mixture is evenly dispersed by high-speed stirring and then dried to obtain a precursor of a composite of graphite and cobalt acetate; the precursor is placed in a tubular furnace, and inert gas nitrogen is introduced into the furnace, and the temperature is increased to 850° C. at a heating rate of 10° C. / min under a nitrogen atmosphere, and the reaction is carried out at this temperature for 6 hours; after the reaction is completed, the temperature is lowered to room temperature under a nitrogen atmosphere.
[0071] Comparative Example 3
[0072] Commercial graphite without any treatment.
[0073] In order to verify the improvement of the low temperature performance of the negative electrode by the material prepared by the present invention, the negative electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were assembled into half cells and full cells respectively, and the assembly methods are as follows:
[0074] (1) Preparation of positive electrode sheet: lithium iron phosphate is used as the positive electrode active material, and the positive electrode active material is mixed with polyvinylidene fluoride (PVDF) as a binder and small particle conductive carbon black (Super P) as a conductive agent in a weight ratio of 98:1:1, N-methylpyrrolidone (NMP) is added, and the system is stirred under the action of a vacuum stirrer until the system is uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil current collector; the aluminum foil current collector coated with the positive electrode slurry is dried at room temperature and then transferred to an oven for drying, and then cut into small discs with a diameter of Φ14 mm using a cutting machine for use.
[0075] (2) Preparation of negative electrode sheet: The negative electrode materials prepared in each embodiment and comparative example were mixed with a conductive agent Super P, a thickener sodium carboxymethyl cellulose (CMC-Na), and a binder styrene-butadiene rubber (SBR) at a mass ratio of 96.6:0.4:1.2:1.8, and deionized water was added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry was evenly coated on the negative electrode current collector copper foil; the copper foil current collector coated with the negative electrode slurry was dried at room temperature and then transferred to an oven for drying, and then cut into small discs with a diameter of Φ14 mm using a cutting machine for standby use.
[0076] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10ppm, battery-grade (referring to the purity level that meets the battery performance requirements) ethylene carbonate (DOL), propylene carbonate (DMC), ethyl acetate (EA), and vinylene carbonate (VC) are mixed in a volume ratio of 78:15:5:2 to form an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L, and the mixture is mixed evenly to obtain an electrolyte.
[0077] (4) Diaphragm: A 12 μm thick polypropylene film (PP) is used as the isolation membrane. It is cut into Φ19 mm diameter discs using a cutting machine. The cutting process may cause burrs and scratches on the diaphragm. Here, it is necessary to select a diaphragm with a complete shape, no burrs and no scratches, and then clean it with anhydrous ethanol and dry it at 50°C for later use.
[0078] (5) Preparation of structural parts: The battery shell adopts 2025 battery shell, and the required battery shell, spring sheet, gasket and other accessories are purchased from Hefei Kejing.
[0079] (6) Lithium sheets: Purchase lithium sheets with a diameter of 14 mm and a thickness of 0.8 mm from Hefei Kejing for backup.
[0080] (7) Half-cell assembly method: assemble from the negative electrode side, negative electrode shell + spring sheet + 0.5 mm Φ 16 mm gasket + lithium sheet + 25 μL electrolyte + diaphragm + 25 μL electrolyte + negative electrode sheet + 0.2 mm Φ 16 mm gasket + positive electrode shell.
[0081] (8) Method for assembling the whole battery: assemble from the negative electrode side, negative electrode shell + spring sheet + 0.5 mm Φ 16 mm gasket + negative electrode plate + 25 μL electrolyte + diaphragm + 25 μL electrolyte + positive electrode plate + 0.2 mm Φ 16 mm gasket + positive electrode shell.
[0082] The lithium-ion battery test method is to charge and discharge at 0.1C / 0.1C for 3 cycles before testing. The test contents are as follows:
[0083] 1) In order to verify the effect of the modification process on the capacity of graphite, a half-cell assembled with a negative electrode was subjected to a complete charge-discharge cycle at 25°C and 0.5C, with a charge cut-off voltage of 1.6V and a discharge cut-off voltage of 0V. The test results are shown in Table 1;
[0084] 2) In order to verify the improvement of the modification process on the graphite dynamics and low-temperature performance, a half-cell assembled with a negative electrode sheet was subjected to a complete charge-discharge cycle at -20°C and 0.5C, with a charge cut-off voltage of 1.6V and a discharge cut-off voltage of 0V. The test results are shown in Table 1;
[0085] 3) In order to verify the low-temperature cycling ability of the modified graphite, a full battery assembled with a negative electrode sheet and a positive electrode sheet was charged and discharged at -20°C at 0.33C / 0.33C, and the capacity retention rate after 100 cls was tested. The test results are shown in Table 1.
[0086] Table 1: Battery performance of Examples 1 to 6 and Comparative Examples 1 to 3
[0087]
[0088] The test results in Table 1 show that the low-temperature discharge gram capacity, low-temperature discharge retention rate and low-temperature cycle capacity retention rate of the batteries assembled in Examples 1 to 6 are significantly improved compared with the batteries assembled in Comparative Examples 1 to 3. This shows that Examples 1 to 6 etch pores inside the graphite particles by high-temperature water vapor etching technology. The presence of the pores reduces the diffusion distance and transmission impedance of lithium ions in the graphite particles, thereby greatly improving the low-temperature performance of the graphite material without reducing the gram capacity.
[0089] Comparing Example 1, Comparative Example 1 and Comparative Example 2, the low temperature performance of Example 1 is better than that of Comparative Example 1 and Comparative Example 2. This is because Comparative Example 1 does not add easily decomposable transition metal salts, and there is no catalytic effect of transition metal oxides in the water vapor etching stage, and it is difficult to form porous graphite; Comparative Example 2 does not pass water vapor, and cannot perform etching reactions, and thus cannot obtain porous graphite. This shows that the formation of porous graphite requires the simultaneous presence of transition metal salts and water vapor.
[0090] The present invention uses high-temperature water vapor etching technology to etch channels in graphite particles to form porous graphite, thereby reducing the diffusion distance of lithium ions inside the graphite particles, thereby reducing the negative electrode impedance and improving the kinetic performance. It can greatly improve the low-temperature performance of the graphite material without reducing the material's gram capacity. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance.
[0091] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a negative electrode material, characterized in that: The following steps are involved: Material mixing: dispersing graphite and transition metal salt into a dispersant, stirring and compounding, and then drying to obtain a precursor; Water vapor etching: placing the precursor in a furnace, and introducing water vapor into the furnace to perform an etching reaction to obtain porous graphite.
2. The preparation method according to claim 1, characterized in that: The transition metal salt includes one or more of transition metal nitrate, transition metal carbonate, transition metal acetate, nickel acetylacetonate, or cobalt acetylacetonate.
3. The preparation method according to claim 2, characterized in that: The general formula of the transition metal nitrate is M(NO3) x1 The general formula of the transition metal carbonate is M(CO3) x2 The general formula of the transition metal acetate is M(CH3COO) x3 , wherein M represents a transition metal, and the M is selected from any one of Co, Ni, Mn, and Cr, and x1≥2, x2≥1, and x3≥2.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the transition metal salt to the graphite is 0.02% to 0.03%; and / or, The dispersant includes one or more of water, ethanol and N,N-dimethylformamide.
5. The preparation method according to claim 1, characterized in that: The water vapor etching step comprises: Heating stage: placing the precursor in a tube furnace, and introducing an inert gas into the tube furnace, so that the tube furnace is heated to a target temperature in an inert atmosphere; Reaction stage: after the tube furnace is heated to the target temperature, water vapor is introduced into the tube furnace, and an etching reaction is performed at the target temperature; Cooling stage: After the etching reaction is completed, the introduction of water vapor is suspended to allow the temperature of the tubular furnace to drop to room temperature in an inert atmosphere.
6. The preparation method according to claim 5, characterized in that: In the heating stage, the heating rate of the tubular furnace is 5 to 10°C / min, and the target temperature of the tubular furnace is 800 to 900°C.
7. The preparation method according to claim 5, characterized in that: In the reaction stage, the volume ratio of the water vapor to the inert gas is 1:9, and the reaction time of the etching reaction is 6 to 8 hours.
8. The preparation method according to claim 1, characterized in that: The drying temperature in the material mixing step is lower than 60°C.
9. A negative electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. The negative electrode material according to claim 9, characterized in that The negative electrode material includes porous graphite, and the pores in the porous graphite extend from the surface of the graphite particles to the inside of the graphite particles.
11. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode material prepared by any preparation method according to claims 1 to 8.
Citation Information
Cited By
Recycling method and application of graphite negative electrode of waste battery
CN121672518A
A method for recycling and regenerating waste battery graphite negative electrode and application
CN121672518B
